Cutter’s Procedure for Specific Subject Indexing - Bhattacharyya, G. (Journal of Information and Knowledge, 1974)
Cutter’s procedure of deriving subject headings for syndetic specific subject indexing in a dictionary catalogue is a specific content of the logical form abstracted in the general theory of subject headings. This can be recognised through the interpretation of the abstract logical form. For this purpose an attempt is made to understand precisely the denotations of the pertinent technical terms used by Cutter in relation to subject indexing. The special attributes of the dictionary catalogue envisaged by Cutter are culled out from his various discussions; and they are systematised. Developments in subject headings that took place prior to Cutter are taken note of with reference to the general theory of subject headings. The study of fundamentals of Cutter’s procedure as a whole, in this context, reveals that his policy for asyndetic subject indexing consists of associative grouping (classification) deeming each specific subject - individual or general, as the case may be - as a base. In the case of a compound subject, all other components, if any, are the complements. His policy for syndetic subject indexing also consists of the same associative grouping. Additionally it consists of introducing an approximation to organising grouping (claSSification) through references without explicit indications of COSSCO-relationships. His explicit rules of procedure are meant for implementing these poliCies. Evidently, there is an implicit set or postulates about the elementary structures of names of subject, which is distilled out. That there is an implicit systematic scheme of subject headings which becomes evident from Cutter’s discussion and examples, is also pointed out. The appliCation of Cutter’s basic rules on the basis of the modulated names-of-subject formulated by using the postulates and the implied scheme, is demonstrated.